Análisis de la calidad de servicio en redes MANET en base a los protocolos de enrutamiento - Cruz Hermosa, Francisco Xavier (2017)
Ad-Hoc mobile networks are a set of devices connected by wireless technology, which have some independent mobility and ease of movement in any direction without the need for pre-existing infrastructures. The dynamic change of their mobile stations allows to study the conditions of link between devices and the behavior of their routing protocols. These wireless networks minimize the use of access points, wired infrastructures and maintenance costs, since each device simultaneously generates communication as a router and final node. Ad-Hoc mobile technology is used in; Various military areas, in places where cable communication is difficult to reach, to rescue people in the event of natural disasters, or where communications services lose their balance. In order to analyze an Ad-Hoc network, several routing algorithms have been created through which different types of dynamism can be generated in the nodes of a network. Two important routing groups have been selected for interpretation, these are: reactive (AODV and DSR) and proactive (DSDV) protocols. Through the simulations created in this work, it will be observed in each of the protocols how many packets they can generate, send, lose and receive within an Ad-Hoc network. For the development of the networks the NS-2, XGRAPH and NSG2 simulation programs were used, with which different tests were carried out to verify the effective channel, delay and loss of packages, in order to obtain clear, accurate and real results To validate the best protocol and quality of service. To finalize the titling work, a manual was developed that will help the user to carry out the installations of the simulation programs and their proper use. A guide will be generated for the reader of this project so that it helps to develop research topics, study and implementation of new applications for Ad-Hoc mobile networks, thus contributing to the technological advancement of these important networks.